Pemberitaan Haji dalam Surat Kabar Pedoman Tahun 1950 - Fasih, Ulum (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2024)
This historical study of Hajj-related news in Indonesia contained in newspapers will answer a general question about why Hajj news in newspapers was published for almost a full year, and what the content of the news published in newspapers for almost a full year was. This study uses a historical method carried out in four stages, namely heuristics, criticism, interpretation, and historiography. The results of this study explain that Hajj news was published to inform Muslims about the government's efforts to organize the Hajj starting from preparation, departure, to return, and to inform Muslims who wanted to perform the Hajj in 1950 regarding the preparations that had to be made.